The interference of the brotherhoods of artisans in organizing guilds in colonial Lima - Fernández Villanova, David (2017)
The general objective of this work is to approach the world of the artisans of Lima through the study of its brotherhoods. The corporatism of the Ancient Regime was a feature especially significant at the artisanal level, with the convergence of the two corporations: the brotherhood and the guild. The objective of this paper is to analyze the role played by the brotherhoods of craftsmen beyond their religious dimensions. Through the study of the ordinances of the brotherhoods of shoemakers and tailors the author shows how religious corporations were used by artisans to gain control of the guild or to legislate labor matters. This was achieved by the brotherhood with their higher moral authority in comparison to the guild.